Numerical Analysis on the Effects of Cavity Geometry with Heat towards Contaminant Removal - Saadun, Mohd Noor Asril; Mokhtar, Nur Hazwani; Zakaria, Mohamad Shukri; Abdul Manaf, Muhammad Zaidan; Mohd Hanafi, Mohd Hafidzal (Trans Tech Publications, 2013)
Contaminants are recently discovered at the joint of large piping system and causing defect to industrial product. A computational analysis can be used as a solution of the hydrodynamic contaminant removal without any modification needed. In this paper, the effect of heat is introduced to analyze the heat transfer and flow field in a channel with cavity heated at the bottom sides coupled with different shape of cavity. The cavity shape used comes with three shapes i.e. square, triangle and semicircle. The process of fluid dynamic in a cavity is modeled via numerical solution of the Navier–Stokes equations using Cubic Interpolated Profile (CIP) method. By using the simulation of hydrodynamic contaminant removal, the flow of streamlines and vortices pattern was investigated in the cavities. In order to remove all of the contaminant, hydrodynamic need to take part in this simulation which is flow from the inlet of the channel and create vortices to remove it from the cavities. The result shows that the percentage of contaminant removal is higher for semicircle cavity with higher Grashof number. The result also indicates that vortices formation is highly dependent on the cavity geometry and creates a buoyancy effect.